ChemInform Abstract: Designing Multielectron Lithium‐Ion Phosphate Cathodes by Mixing Transition Metals. Issue 33 (25th July 2013) - Hautier, Geoffroy; Jain, Anubhav; Mueller, Tim; Moore, Charles; Ong, Shyue Ping; Ceder, Gerbrand
Abstract Ab initio computations in the DFT framework for mixtures of different transition metal oxides capable of acting as electrode material for lithium batteries are presented.